Effect of Carbon and Nitrogen Cources of the Medium used to Grow Biocontrol Strain UTPF61 of Pseudomonas fluorescens on its Protective Activity Against Sclerotinia Wilt of Sunflower and its Survival During and after the Formulation Process. Issue 1 (2013) - Heidri-Tajabadi, Fereshteh; Ahmadzadeh, Masoud; Fallahzadeh-Mamaghani, Vahid; Moeinzadeh, Asma
No abstract available